Life's Simple 7 Cardiovascular Health Metrics and Progression of Coronary Artery Calcium in a Low-Risk Population: A Cohort Study. Issue 4 (April 2019) - Kim, Seolhye; Chang, Yoosoo; Cho, Juhee; Hong, Yun Soo; Zhao, Di; Kang, Jeonggyu; Jung, Hyun-Suk; Yun, Kyung Eun; Guallar, Eliseo; Ryu, Seungho; Shin, Hocheol
Abstract : Objective—: We examined the association of cardiovascular health (CVH) metrics with the development and progression of coronary artery calcium (CAC) among apparently healthy adults. Approach and Results—: This cohort study included 65 494 men and women 30 years of age and older free of cardiovascular disease at baseline who underwent a comprehensive exam including CAC scoring. CVH metrics were defined according to the American Heart Association Life's Simple 7 metrics based on smoking, diet, physical activity, body mass index, blood pressure, total cholesterol, and fasting glucose. CVH scores range from 0 (all metrics considered unhealthy) to 7 (all metrics considered healthy). Participants were followed-up for a maximum of 6.6 years. Compared with participants with ideal CVH scores 0–1, the multivariable-adjusted difference in the change in geometric means of CAC scores over 5 years of follow-up were −0.40 (−0.62 to −0.19), −0.83 (−1.03 to −0.63), −1.06 (−1.25 to −0.86), −1.22 (−1.42 to −1.03), and −1.05 (−1.42 to −0.69) in participants with ideal CVH scores 2, 3, 4, 5, and 6–7, respectively. The inverse association between CVH scores and progression of CAC was observed both in participants with no CAC and in those with CAC detectable at baseline. Conclusions—: A higher ideal CVH metrics score was strongly associated with a lower prevalence of CAC and with lower progression of CAC in males and females in a large cohort of healthy adults. Our findings suggest that maintaining a healthy life habits could help reduce the development and progression of subclinical atherosclerosis and ultimately prevent clinically cardiovascular event. Abstract : Supplemental Digital Content is available in the text.